Psychometric Properties of the Indonesian Dialysis Thirst Inventory in Hemodialysis Patients: A Rasch Analysis - Yudi Triguna; Dewi Aryanti; Deny K. Sunjaya; Mohammad Faris K.L.Harahap; Ida Rosdiana; Peni Cahyati (Media of Health Research, 2026)
Although thirst severely impacts hemodialysis patients, a validated Indonesian measurement tool remained unavailable, limiting standardized clinical assessments. This study aimed to evaluate the validity and reliability of the Indonesian Dialysis Thirst Inventory (DTI) using Rasch analysis. A cross-sectional design involved 145 hemodialysis patients from two Indonesian centers. Following a cross-cultural translation protocol, psychometric properties were analyzed using Winsteps software. The results confirmed strong unidimensionality, with 77.8% of variance explained by Rasch measures. All seven items fit the model well, showing a mean outfit mean-square of 0.98. The instrument demonstrated excellent reliability (person = 0.92, item = 0.99) and a person separation index of 3.42, which discriminated four distinct levels of thirst severity. Furthermore, differential item functioning analysis indicated minimal gender bias. In conclusion, the Indonesian DTI proved to be a highly valid and reliable instrument. Its implementation provided a standardized method for comprehensively assessing thirst, yielding crucial data to guide targeted fluid management interventions and prevent interdialytic weight gain in hemodialysis care.